Gut-muscle axis mechanism of exercise prevention of sarcopenia - Li, Tao; Yin, Danyang; Shi, Rengfei (Frontiers in Nutrition, 2024)
Sarcopenia refers to an age-related systemic skeletal muscle disorder, characterized by loss of muscle mass and weakening of muscle strength. Gut microbiota can affect skeletal muscle through a variety of mechanisms. Gut microbiota present distinct features among the elderly and sarcopenia patients, including the decrease of microbial diversity, which might be associated with the quality and function of the skeletal muscle. There might be a gut-muscle axis, gut microbiota and skeletal muscle may affect each other bi-directionally. Skeletal muscle can affect the biodiversity of gut microbiota, and the latter can in turn affect the anabolism of skeletal muscle. This review examines recent studies exploring the relationship between gut microbiota and skeletal muscle, summarizes the effects of exercise on gut microbiota, and discusses the possible mechanisms of the gut-muscle axis.